Fauna flebotomínica em áreas de transmissão da Leishmaniose tegumentar americana na Bacia do Rio Araguari, no município de Uberlândia, Minas Gerais, Brasil: um estudo de geografia médica - Lemos, Jureth Couto (2002)
American cutaneous leishmaniasis - LTA has caused serious problems to people’s health all around the country. This work has the objective to present some studies on Medicai Geography and on infector-parasite diseases. It shows data about the environment aspects, the phlebotominic fauna and the seasonal variation of the phlebotomine in the transmition areas of LTA in the Araguari River Basin, in Uberlândia, Minas Gerais. The work intends to suggest environmental vigilance measures conceming to health as a preventive measure and disease control. Medicai Geography aims to study the distribution and prevalence of diseases in the world. Eleven places were identified as occurrence areas of LTA in the Araguari River Basin in the city of Uberlândia. Data were taken from the patients records which were diagnosed as having LTA. (autochthonous cases) In those places from October 7th, 1999 iq January 18th, 2001, 60 phlebotomine were captured in 226 hours. Capturing the phlebotomine. CDC (Center on Disease Control) and Shannon traps were used in which 8,657 phlebotomine were caught. They belong to two genders, (Lutzomyia and Brumptomyia\ 13 species being 2,284 male and 6,373 female. The prevalent species was Lutzomyia intermedia, with 8 602 phlebotomine, representing 99.36%, while the other species accounted for 0.64%. To observe the insects’ seasonal variation 4 fifteen-hour collecting were made (from 4 p.m. to 7 a.m.) in four periods of the year, that is, humid (May, 2000), Cold and dry (June, 2000), Warm and dry (October, 2000) and Warm and rainy (January, 2001). Lutzomyia intermedia was the species found as the vector, responsible for the transmission of LTA in the city of Uberlândia. For that reason there is the necessity of a Health Environmental Vigilance System implantation with preventive measures to control phlebotomine in order to diminish the risk of increasing the human cases of that disease in the city of Uberlândia.